2010
DOI: 10.1093/humrep/deq311
|View full text |Cite
|
Sign up to set email alerts
|

Elevated immunoreactivity to tissue factor and its association with dysmenorrhea severity and the amount of menses in adenomyosis

Abstract: These results suggest that TF is involved in adenomyosis-associated heavy menstrual bleeding and dysmenorrhea and thus may be a potential therapeutic target in treating symptomatic adenomyosis and perhaps also chronic pelvic pain in women with adenomyosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 64 publications
2
53
0
1
Order By: Relevance
“…The endometrial expression and activation of F3 has been reported to increase endometrial cell proliferation and IL6 and IL8 secretion (34). In addition, increased expression of IL8 and F3 has been associated with heavy menses and abnormal uterine bleeding in progestin-onlycontraceptives users (47)(48)(49). Considering the F3-induced activation of prothrombin to thrombin is a key step in coagulation cascades (50) and regulated by proinflammatory mediators such as IL8, miR-93/106b regulation of either F3 and/or IL8 may have a profound biological and clinical significance, specifically in women with symptomatic leiomyomas experiencing abnormal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The endometrial expression and activation of F3 has been reported to increase endometrial cell proliferation and IL6 and IL8 secretion (34). In addition, increased expression of IL8 and F3 has been associated with heavy menses and abnormal uterine bleeding in progestin-onlycontraceptives users (47)(48)(49). Considering the F3-induced activation of prothrombin to thrombin is a key step in coagulation cascades (50) and regulated by proinflammatory mediators such as IL8, miR-93/106b regulation of either F3 and/or IL8 may have a profound biological and clinical significance, specifically in women with symptomatic leiomyomas experiencing abnormal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The patients recruited to this study were reported previously [21,22]. Briefly, 50 women with histologically confirmed adenomyosis (excluding endometriosis) seen at the Shanghai Obstetrics and Gynecology Hospital, Fudan University, Shanghai, China, were recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for immunohistochemistry analysis, including the quantification method, used for this study was identical to the one in our previous studies [21,22]. Briefly, serial 4-µm sections were obtained from each block, with the first resultant slide being stained for HE to confirm pathologic diagnosis, and the subsequent slides stained for HDAC1–3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been a challenge for the effective treatment of adenomyosis. Clinically, hysterectomy was usually used for the treatment of severe adenomyosis; however, this would lead to loss of fertility and severe trauma in patients suffering from this operation [6,7]. Alternative therapeutic strategies include gonadotrophinreleasing hormone (GnRH) agonists and some other therapeutic options; nevertheless, these therapeutic administrations possess generally specific shortages, such as short duration and frequent relapse [7,8].…”
Section: Introductionmentioning
confidence: 99%